Model Kepemimpinan Gembala Sidang dalam Terang Narasi Teologis Injil Yohanes dan Masukan Praktis Bagi Gereja Lokal - Eliezer Andelta Sinukaban (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christian leadership can be understood as leadership rooted in the truth of God’s Word and exemplified through the life and ministry of Jesus Christ. In the Gospel narratives, Jesus consistently displayed leadership qualities that were grounded in service, sacrifice, humility, and the nurturing of His disciples. However, in today’s context, many church environments face a crisis of leadership characterized by corruption, arrogance, lack of integrity, and resistance to constructive criticism, all of which deviate from the biblical image of Christ as the Good Shepherd. This study aims to explore the biblical foundation of Jesus Christ’s leadership, focusing on both its character and technical dimensions as reflected in the Gospel of John, and to examine its implementation in the local ministry setting of GPdI Bethesda Kabanjahe. The research employs a qualitative method with two primary dimensions: a theological-biblical approach and a case study approach. The findings reveal that, first, the pastoral leadership model in the Gospel of John presents Jesus as the Good Shepherd who builds intimate relationships, willingly sacrifices, and develops the character of His followers. While these values are normatively acknowledged by church ministers, their implementation in GPdI Bethesda remains partial, fragmented, and not yet systematically embedded into the overall ministry structure. Second, theological reflection and practical implications highlight the urgent need for renewal that encompasses both organizational systems and the personal spiritual formation of leaders. Recommendations emerging from this study include leadership training grounded in Christlike character, developing an organizational structure that ensures regeneration, cultivating a healthy spiritual community, and contextually internalizing Gospel values into ministry practices. Strengthening these areas is essential for building authentic, sustainable, and Christ-centered leadership that responds to contemporary challenges and restores the church’s witness to the surrounding community.